Innowacyjność przedsiębiorstw w kontekście zmian l doskonalenia organizacji - Brojak-Trzaskowska, Małgorzata (Innovativeness of enterprises regarding changes and organizations improvement, 2006)
The main aim of that paper is to discuss chosen aspects of enterprise innovativeness. The elimination of threatens coming from surroundings and weak points of enterprise, but also playing up opportunities and strong points influence enterprise development. The major initiator of modem enterprises development should be their innovativeness. Nowadays enterprise survival, its development and competitive advantage mostly depend on inspiring innovative projects, that should not be concentrate on products or processes, but every area of enterprise functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 347-353